Mobility Where Mobility is Illegal: Migration and City Growth in the Soviet Union - Ira N. Gang; Robert C. Stuart (Rutgers University, Department of Economics, 1998)
his paper examines an important anomaly in the internal migration history of the former Soviet Union (FSU). While many cities were closed in the sense of explicitly limiting growth of city population from migration, it was difficult to assess the effectiveness of these controls. We analyze a sample of 308 Soviet cities to isolate the impact of closure regulations controlling for city size. We find that while there are pervasive patterns of city growth, the rate increasing through the 1960s and declining thereafter, there are also pervasive differences between controlled and uncontrolled cities, the later growing significantly faster in almost all cases, controlling for city size.
Keywords: J6; P20; R23; 330; cities; city growth; fsu; migration; urbanization